Differentiated Learning with the STEAM Learning Model Towards School Well-Being - Isnaindita, Oktadella Maulida Nur; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to investigate the impact of integrating differentiated learning with the STEAM (Science, Technology, Engineering, Arts, and Mathematics) framework on elementary students' school well-being. It addresses pressing educational challenges in 21st-century Indonesia, particularly in response to low performance indicators highlighted in the 2018 PISA results, by exploring innovative learning methodologies that can foster critical, creative, and collaborative thinking. Methodology: A quantitative research approach was used to statistically analyze the effect of STEAM-based differentiated learning (independent variable X) on student school well-being (dependent variable Y). The research was conducted among 4th and 5th-grade students from two elementary schools in Surakarta—SD Muhammadiyah 16 Karangasem and SD IT Insan Mulia—using a simple random sampling method to select 220 participants. Data were analyzed using simple regression analysis and t-tests to assess the significance of the learning model’s impact on the four dimensions of school well-being. Results: The analysis revealed that the integration of STEAM and differentiated learning had a statistically significant positive influence on students’ well-being in school, particularly across the dimensions of having, loving, being, and health. The results of both the regression and t-tests showed significance values between 0.000 and 0.006, all of which are below the threshold of 0.05, confirming that STEAM-based differentiated learning contributes meaningfully to enhancing student well-being. Applications/Originality/Value: The study highlights the practical application of STEAM-based differentiated learning as a viable strategy for improving student well-being in elementary education settings. It provides empirical evidence that such an integrated approach not only addresses cognitive development but also supports students’ emotional and social needs within the school environment. These findings offer valuable insights for educators and policymakers seeking to implement holistic, student-centered learning innovations in Indonesian schools and similar educational contexts globally.